Pseudospin and spin symmetries in the relativistic harmonic oscillator - Albertoa, P.; Castro, A. [UNESP]; Malheiro, M.; Lisboa, R. (My University, 2006)
We compute the analytical solutions of the generalized relativistic harmonic oscillator in 1+1 dimensions, including a linear pseudoscalar potential and quadratic scalar and vector potentials which have equal or opposite signs These are the conditions in which pseudospin or spin symmetries can be realized We consider positive and negative quadratic potentials and present their bound-state solutions for fermions and an-tifermions. We relate the spin-type and pseudospin-type spectra through charge conjugation and γ5 chiral transformations. Finally, we establish a relation of the solutions found with single-particle states of nuclei described by relativistic mean-field theories with tensor interactions and discuss the conditions in which one may have both nucleon and antin-ucleon bound states.
Keywords: Bound state; Charge conjugation; Relativistic harmonic oscillators; Relativistic mean-field theories; Scalar and vector potentials; Single particle state; Spin symmetry; Tensor interaction; Elementary particles; Mean field theory; Oscillators (mechanical)